Changes in growth performance and critical components of the Somatotropic growth axis in growing pigs after infection with Salmonella enterica serovar Typhimurium or Choleraesuis - Davis, Brian Lee (Kansas State University, 2008)
Enteric disease and immune challenge are processes that have detrimental effects on growth performance of young swine. The current study tested the hypothesis salmonellae-induced enteric disease would perturb the endocrine growth axis in a serovar dependent fashion. Specifically, we evaluated effects of Salmonella enterica serovar Typhimurium (Typhimurium) and serovar Choleraesuis (Choleraesuis) on critical regulatory components of growth in young swine. Weaned pigs were housed 2 per pen with ad libitum access to feed and water in a 14 d experiment. Pigs were then repeatedly fed either 10[superscript]8 CFU Choleraesuis or 10[superscript]8 Typhimurium in dough balls, with control pigs receiving dough without bacteria. Bacteria were re-fed twice weekly. Rectal temperatures were monitored daily from d 0 to7 and ADFI was measured through d 14. Pigs were weighed and samples of serum were obtained for circulating IGF-I on days 0, 7, and 14. At the conclusion of the study, samples of semitendinosus muscle and liver were obtained and subsequently assayed for IGF-I, IGFBP-3, and IGFBP-5 mRNA. Rectal temperatures were elevated in pigs given Choleraesuis pigs from d 2 through d 7 (P < 0.05) when compared to control pigs and pigs fed Typhimurium. Pigs receiving Choleraesuis had substantially decreased feed intake on days 2, 3, 4, 7, 8, 9, and 10 (P < 0.01), with a trend for reduction on d 5 (P = .08), and they experienced an approximate 25% reduction in BW compared to control and Typhimurium pigs by the conclusion of the study. Pigs given Choleraesuis also experienced marked reductions in circulating IGF-I on d 7 (P < 0.01 vs. control and Typhimurium) with reductions of lesser magnitude on d 14 (P = 0.07 vs. control and P < 0.05 vs. Typhimurium). Treatment tended to affect liver IGFBP-3 mRNA (P = 0.08), where expression tended to be elevated in Typhimurium and Choleraesuis pigs. In contrast, IGFBP-3 mRNA relative abundance was increased (P < 0.03) in pigs given Typhimurium versus control pigs. Muscle IGF-I mRNA was reduced in Choleraesuis pigs compared to control and Typhimurium (P < 0.05). Treatment tended to affect muscle IGFBP-3 mRNA (P = 0.10), where Choleraesuis had numerically less relative abundance than controls. Oral inoculation of growing pigs with Choleraesuis disrupted feed intake and BW gain, and this was accompanied by decreases in circulating IGF-I and reduced muscle expression of mRNA for IGF-I and IGFBP-3.
Keywords: Salmonella; Swine; IGF-I; IGFBP-3; Agriculture, Animal Pathology (0476)